Rancang Bangun Alat Pemotong Keripik Ubi Jalar dengan Sistem Penggerak Pulley Menggunakan Motor Listrik 0,5 Hp - Kusuma, Muhammad Dewantara; Abdi, Ferly Isnomo; Wulandari, Diah; Ganda, Andita Nataria Fitri (Universitas Negeri Surabaya, 2023)
In using a manual sweet potato chip cutter, expertise and experience are required so that the sweet potato pieces are uniform and not too thick or thin. This tool also takes quite a lot of time and energy if used to cut in large quantities. In previous studies, several chip cutting tools have been made, but the tools made have large dimensions and to cut sweet potatoes require a push from the hand. Based on this background, the researcher made a sweet potato chip cutter using an electric motor in this case, it can be reduced in size or use lighter materials but still strong and durable. The result of the Design of Sweet Potato Chips Cutting Machine is this sweet potato chips cutting machine has dimensions of 75 cm long, 40 cm wide, and 75 cm high. This machine uses an electric motor of 0.5 Hp with an electric motor speed of 1400 rpm and this machine is capable of producing 31.175 kg / hour pieces.